Analisis Peran Indonesia Dalam Implementasi Human Rights Due Diligence (HRDD) Sesuai Visi Asean Economic Community Blueprint 2025 - Stefan Lamuel Ayub; Triesanto Romulo Simanjuntak; Putri Hergianasari (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This research was conducted to find out and analyze what roles have been carried out by the Indonesian government in the process of implementing Human Rights Due Diligence in accordance with the vision contained in the ASEAN Economic Community Blueprint 2025. This research was conducted using descriptive analysis method to observe data relevant to the HRDD implementation process conducted by Indonesia. The implementation by the Indonesian government itself is based on the Guidelines on Business and Human Rights recommended by the United Nations. The results of the research found that the implementation of HRDD in Indonesia is carried out in accordance with the 3 pillars in the UNGPs 2011 and also the vision of humanity in the ASEAN Economic Community Blueprint 2025.